Fungicide resistance against fluopyram in Alternaria solani - Ekdahl, Felicia (SLU/Dept. of Plant Protection Biology, 2022)
Early blight in potato production can be devastating and to minimize crop damage the use of fungicides has been the key. New fungicides called the SDHIs have been used against the early blight pathogen, Alternaria Solani in potato fields to reduce yield losses. However, repeated fungicide applications run the risk of fungicide resistance development in the fungal population, through the selection of mutations in the genes that are targeted by the fungicides. Mutations that confer a loss of sensitivity to the fungicide (i.e., fungicide resistance) will be selected for in fungal populations where there is a significant selection pressure, through for example, the repeated use of one class of fungicides. To investigate whether A. solani was becoming insensitive to the new SDHI fungicide fluopyram, a growth study was conducted where 20 different strains of A.solani were grown on solid medium with five different concentrations to see if some of the strains were less susceptible than others. It was difficult to draw in depth conclusions from this growth study, however some samples showed less sensitivity to the fluopyram. A DNA analysis of the fluopyram target gene was also performed to try to determine if there were any mutations associated with resistance present. However, due to problems with the PCR and sequencing experiments it was not possible to make any firm conclusions from this.